Developing Collaborative Communicators: A Qualitative Case Study of Student-Scientist Partnerships and Project-Based Learning Experiences - Maggie Murphy; Jamie Loizzo; Whitney Stone (Journal of Applied Communications, 2025)
As scientists are called upon to communicate their research, it is important to prepare upcoming science communicators to collaborate with science experts to develop effective communication. Agricultural and natural resources (ANR) communication college students could gain experience working with scientists through project-based learning (PjBL). However, little is known about the experiences of scientists and students collaborating in PjBL courses. The study evaluated scientists’ past science communication experiences, how they prepare to communicate with the public, and their perceptions of collegiate students’ science communication projects featuring their research. We conducted pre-/post-interviews with ANR scientists (n = 18) who participated in student-created photo essays and electronic field trips via three PjBL courses. Results included the following themes: a) Scientists’ past science communication experiences were influenced through media consumption and education, sharing science with others, and prior work experiences before their current position, b) Some scientists did not prepare for science communication and engagement, while others tailored their messages to the audience and practiced ahead of time, c) Scientists were satisfied with the overall products the students created, yet they suggested future improvements to time management and writing quality. Future recommendations include science communication training for scientists to: a) develop skills in simplifying complex scientific concepts while maintaining accuracy and building confidence and b) tailor the message to the audience, with adjustments to language, content depth, and delivery style. Finally, we recommend implementing an ANR communication PjBL curriculum to foster collaboration between scientists and college students, co-constructed communication, and real-world project development.
Keywords: project-based learning; science communication; scientists; students; collaboration; media; multimedia; writing; interviews; electronic field trips; communication training